(untitled) (International Journal of Medicine and Medical Sciences, 2020)
Exposure to excessive monosodium glutamate (MSG) during neonatal life has been correlated with loss of function in stress response that might be involved in changes of adrenal activity. This study was designed to investigate the protein pattern and examine the mRNA level of proteins in the adrenal glands following MSG stimulation. Neonatal rats were subcutaneously administered with MSG at a concentration of 4 mg/g body wt for 15 days and adrenal glands were collected. Analysis of 2D-PAGE of adrenal extracts demonstrated that MSG induces an increase expression of HSC70, GRP75 and GRP78. In addition, MSG treatment affected to the pI of ALDH2 to more acidic. Semi-quantitative RT-PCR showed an up -regulation of HSC70 and GRP78 transcripts in adrenal gland of MSG-treated rats, while there were no changes in GRP75 and ALDH2 mRNA levels. This study showed that administration of MSG affects on adrenal gland at both level of protein expression and gene expression differentially suggesting a complex responding process of adrenal gland to MSG stimulation.